2021
DOI: 10.1002/ijc.33828
|View full text |Cite
|
Sign up to set email alerts
|

A robust and interpretable gene signature for predicting the lymph node status of primary T1/T2 oral cavity squamous cell carcinoma

Abstract: Oral cavity squamous cell carcinoma (OSCC) affects more than 30 000 individuals in the United States annually, with smoking and alcohol consumption being the main risk factors. Management of early-stage tumors usually includes surgical resection followed by postoperative radiotherapy in certain cases. The cervical lymph nodes (LNs) are the most common site for local metastasis, and elective neck dissection is usually performed if the primary tumor thickness is greater than 3.5 mm. However, postoperative histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Interestingly, 23% of published breast cancer signatures showed a weaker association with outcome than the median of the random signatures of the same size 53 , 54 . Therefore, we used combined k-top scoring pairs (k-TSPs) 55 , 56 , leave-one-out single gene removal (SGR) and single gene significance analysis to identify a nine-gene subset of ET-60, henceforth referred as ET-9 (Table 1 , Supplementary Fig. 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, 23% of published breast cancer signatures showed a weaker association with outcome than the median of the random signatures of the same size 53 , 54 . Therefore, we used combined k-top scoring pairs (k-TSPs) 55 , 56 , leave-one-out single gene removal (SGR) and single gene significance analysis to identify a nine-gene subset of ET-60, henceforth referred as ET-9 (Table 1 , Supplementary Fig. 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, we have shown that such mechanistic signatures derived from microarrays or RNA-Seq studies can be implemented using technologies such as RT-PCR, which further increases their translational value. 37 …”
Section: Discussionmentioning
confidence: 99%
“…To accomplish this, we used gene expression profiles from 369 pre-NACT TNBC samples, of which 223 samples were used for training and the remainder for testing. We leveraged our group's recent demonstration of the importance of incorporating biological constraints in predictive classifiers [9,42] and used this approach to identify a subset of features predictive of NACT response. Specifically, we first designed a biological mechanism capturing the Notch signaling network by pairing genes known to be upregulated with those downregulated by Notch signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these findings support the validity of our approach in the development of predictive classifiers amenable to an effective translation to clinical practice. As such, classifiers developed using this method can be easily implemented as a clinical test using real-time polymerase chain reaction, even when trained on gene expression profiles from microarrays or RNA-seq [42].…”
Section: Discussionmentioning
confidence: 99%